The Precarity of Extracurricular Education in Ontario Schools during Labour Strife - Sefton, Terry (Canadian Journal of Educational Administration and Policy / Revue canadienne en administration et politique de l’éducation)

(untitled) (Department of Educational Administration, University of Saskatchewan, 2022)
Labour strife in the education sector in Ontario has repeatedly highlighted the precariousness of certain types of teaching and learning that are delivered under the catch-all designation extracurricular. This paper reviews education legislation in Ontario over the past 40 years that has impacted teachers’ right to strike; examines how teacher unions and the provincial government targeted extracurricular activities during collective bargaining; and considers how extracurricular activities have come to be an expected part of public education.